OPTIMALITAS PRODUKSI PERTANIAN OPEN FIELD MENGGUNAKAN ALGORITMA SIMPLEKS - Firdaus, Ridwan Awalian; ., Janudin (Universitas Muria Kudus, 2025)
This research is an application of the simplex algorithm in the agricultural sector. The variables of this study are the number of trees that must be planted from the following types of plants: servo tomatoes (Solanum Lycopersicum), bonanza corn (Zea Mays Saccharata Sturt), red chili (Capsicum Annum L), purple eggplant (Solanum Melongena L), and kabocha pumpkin (Cucurbita Maxima L.). The objective function is how much maximum profit is known by knowing the profit parameters for each tree. At the same time, the constraint function is the limitation of resources including land area, water requirements, and production costs. This study aims to determine the optimum profit of open-field agricultural products as well as to find out how many trees should be planted in a planting season plan. This type of research is quantitative and uses data collection methods, namely observation and interviews. The optimization method used is a linear program with the simplex method with the help of the LINGO 19.0 application. The results of the study obtained a maximum profit of Rp. 76,422,000. This value is Rp 8,605,750 greater than the farm's planning. The optimal number of trees to be planted is 950 (tomatoes), 1250 (corn), 550 (red chili), 591 (eggplant), and 319 (pumpkin).